Ensino de suporte básico de vida para estudantes de Medicina: aprendizagem e retenção do conhecimento relacionados ao uso de manequins de alta fidelidade e duração do treinamento - DETOMI, C. A. D. (2019)
Introduction: Basic Life Support (BLS) can be defined as a set of cognitive and motor skills for the maintenance, support or restoration of oxygenation, ventilation and circulation in patients with cardiac arrest, respiratory arrest or both. Simulation is one teaching / learning strategy used to train these skills. Objective: This study aimed to evaluate the learning of BLS skills, especially cardiopulmonary resuscitation skills in adults, children and infants, using different strategies regarding the duration of training and the use of high and low fidelity manikins in students of medicine. Methods: students from the University Center Presidente Tancredo de Almeida Neves - UNIPTAN, in São João del Rei, from the first and second periods received differentiated trainings regarding the time and the use of manikins in practical classes of BLS and were evaluated in a theoretical and practical way, theoretical knowledge and skills acquired at the end of the training. After 3 months, students from the second period were re-evaluated to verify the retention of this knowledge. Thirty-four students from the first period and 52 students from the second period participated in the study. Results: the students who were trained in BLS, for a long time, presented the best performances in the theoretical and practical tests, independently of the manikins used; however, the best results were obtained by students trained in BLS, for a long time, on high fidelity manikins; as well as the evaluation of knowledge retention in BLS, three months after initial training there was a better individual performance in the practical evaluation of students trained in high fidelity manikins. Conclusion: a longer training period and the use of high fidelity manikins in Basic Life Support teaching provided improved learning and retention of knowledge in undergraduate medical students.